A whole-of-population study of the prevalence and patterns of criminal offending in people with schizophrenia and other mental illness - Morgan, V.; Morgan, F.; Valuri, G.; Ferrante, Anna; Castle, D.; Jablensky, A. (2013)
Background Large epidemiological studies are needed to better understand the prevalence and profile of offending by people with mental illness. This study used a whole-of-population design to examine the prevalence, type and pattern of offending across all psychiatric diagnoses, including schizophrenia, compared to the general population. Method We used whole-of-population longitudinal record-linked data for a cohort of all Western Australians born 1955-1969 to determine arrest history over the period 1985-1996 and to ascertain recorded history of psychiatric illness. Of the cohort, 116 656 had been arrested and 40 478 were on the psychiatric case register. Results The period prevalence of arrest for people with any psychiatric illness was 32.1%. The highest arrest prevalence, by diagnostic category, was for substance use disorders (59.4%); the prevalence for schizophrenia was 38.7%. Co-morbid substance use disorders significantly increased risk of arrest in people with schizophrenia. The prevalence of mental illness among offenders was 11.1%: 6.5% of offenders had substance use disorders and 1.7% had schizophrenia. For the majority of offenders with a psychiatric illness, first arrest preceded first contact with mental health services; for schizophrenia only, this proportion was increasing over time. The mean percentage annual change in the number of arrests during 1985-1996 rose significantly for offenders with a psychiatric illness other than schizophrenia and dropped significantly for those with no mental illness. Compared to non-psychiatric offenders, offenders with schizophrenia were more likely to offend alone, to offend in open places and to target strangers. Conclusions Our findings open the way to an informed approach to the management of offenders with mental illness. Copyright © Cambridge University Press 2012.